Effect on health-related quality of life of the X-Bolt dynamic plating system versus the sliding hip screw for the fixation of trochanteric fractures of the hip in adults: the WHiTE Four randomized clinical trial - Griffin, X; Achten, J; O'connor, HM; Cook, J; Costa, M (British Editorial Society of Bone and Joint Surgery, 2021)
Aims Surgical treatment of hip fracture is challenging; the bone is porotic and fixation failure can be catastrophic. Novel implants are available which may yield superior clinical outcomes. This study compared the clinical effectiveness of the novel X-Bolt Hip System (XHS) with the sliding hip screw (SHS) for the treatment of fragility hip fractures.